Textiles and Clothing Sustainability Sustainable Textile Chemical Processes - Muthu, Subramanian Senthilkannan (Textile Science and Clothing Technology,, 2017)
This book highlights the challenges in sustainable wet processing of textiles, natural dyes, enzymatic textiles and sustainable textile finishes. Textile industry is known for its chemical processing issues and many NGO's are behind the textile sector to streamline its chemical processing, which is the black face of clothing and fashion sector. Sustainable textile chemical processes are crucial for attaining sustainability in the clothing sector. Seven comprehensive chapters are aimed to highlight these issues in the book.